Компаративний аналіз діяльності релігійних організацій у Криму та на Закарпатті в ХІХ – на початку ХХІ ст.: новітня українська історіографія - Орлов, Владлен; Orlov, Vladlen (My University, 2015)
У статті проаналізовано історичні праці стосовно релігійного фактора в Криму та на Закарпатті. Констатовано наявність значного корпусу науково-історичних досліджень, які сформувались у період незалежної України. Наголошено, що Крим і Закарпаття мають свої унікальні релігійні атрибути, які відрізняють ці регіони від інших українських земель.The article analyzes the historical research on the religious factor in the Crimea and the Transcarpathia. Ascertained the presence of a significant body of scientific and historical research, which were formed in the period of independence of Ukraine. With the help of a comparative analysis of the laws and characterized by features of the implementation of religious policies in the two regions: the Transcarpathian region and in the Crimea, which are reflected in the new Ukrainian historical studies.
The Comparative Analysis of the Activity of Religious Organizations in the Crimea and the Transcarpathia in 19th - Beginning of the 21st Centuries: the Modern Ukrainian Historiography
Keywords: Закарпаття; історіографія; історія релігії та церкви в Україні; компаративний аналіз; Крим; сучасна українська історіографія; Transcarpathia; historiography; the history of religion and the Church in Ukraine; comparative analysis; the Crimea; the modern Ukrainian historiography